2010
DOI: 10.1007/s00280-010-1461-3
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interactions between peloruside A and other microtubule-stabilizing and destabilizing agents in cultured human ovarian carcinoma cells and murine T cells

Abstract: Combining two microtubule-targeting agents with different binding sites does not guarantee a synergistic interaction in cells, and additional factors are likely to be involved. This study highlights the importance of preclinical testing of actual combinations of drugs before proceeding into clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 33 publications
3
43
0
Order By: Relevance
“…9,12 In addition, laulimalide can displace bound peloruside A, 8 and laulimalide and peloruside A are not synergistic in combination with each other, but only with paclitaxel binding site ligands. 11 These results indicated that peloruside A and laulimalide likely share a new binding site, distinct from the paclitaxel site, and possibly act via mechanisms of stabilization distinct from paclitaxel. This binding site is the second for stabilizing drugs, and the fourth of the four mentioned above.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…9,12 In addition, laulimalide can displace bound peloruside A, 8 and laulimalide and peloruside A are not synergistic in combination with each other, but only with paclitaxel binding site ligands. 11 These results indicated that peloruside A and laulimalide likely share a new binding site, distinct from the paclitaxel site, and possibly act via mechanisms of stabilization distinct from paclitaxel. This binding site is the second for stabilizing drugs, and the fourth of the four mentioned above.…”
Section: Introductionmentioning
confidence: 85%
“…This is known from studies that indicate synergy between peloruside A or laulimalide and other microtubulestabilizing drugs, all of which bind at the paclitaxel binding site, [9][10][11]23 as well as from direct binding studies that have shown that microtubules formed in vitro and taxol-saturated can still bind peloruside A and vice-versa. 8,21 These results demonstrated that the binding site for peloruside A and laulimalide was a new drug site on tubulin, but did not indicate where on tubulin it might be.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…These include dose-limiting toxicities (3-5) and problems with vehicle (31). Synergistic interactions between peloruside and the taxane site drugs have been previously described in vitro in cultured cancer cell lines (32,33).…”
Section: Properties Of Pelorusidementioning
confidence: 99%
“…Peloruside at 5 mg/kg in combination with docetaxel at 6.3 mg/kg gave a TGI of 99%, a value greater than the single-agent values for peloruside of 88% and docetaxel of 19%, suggesting possible synergistic interactions between the 2 MSAs. Because different concentrations of peloruside and taxanes were not tested on tumor growth in vivo, a true synergy calculation was not able to be carried out (32,33).…”
Section: Properties Of Pelorusidementioning
confidence: 99%